Pengaruh Thin Capitalization, Assets Mix, dan Komisaris Independen terhadap Penghindaran Pajak - Ing Wulan Maruti; Luh Nadi (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
This purpose of this research is to analyse the influence thin capitalization, assets mix, and independent commissioner against tax avoidance. This population in this study are consumer goods sector companies being listed in Indonesian Stock Exchange during period 2016 – 2021 with total 30 observation used as sample consisting of 5 companies with research period of 6 years selected by purposive sampling method. The data used on this study are secondary data based on IDX and company official website. The method used in this study are mixing documentation and literature study. The methodology used in this research is the multiple regressions by dated panel regression. The result of this study show that simultaneously thin capitalization, assets mix, and independent commissioner are influence tax avoidance. The other result of this study show that partially thin capitalization, assets mix, and commissioner independent are influence tax avoidance.